Pesticides and Parkinson’s Disease - Sherer, Todd B. (ScientificWorldJournal, 2001)
Parkinson’s disease (PD), a common neurodegenerative disorder affects approximately 1% of the population over 65. PD is a late-onset progressive motor disease characterized by tremor, rigidity (stiffness), and bradykinesia (slowness of movement). The hallmark of PD is the selective death of dopamine-containing neurons in the substantia nigra pars compacta which send their projections to the striatum and the presence of cytoplasmic aggregates called Lewy bodies [1-2]. Most cases of PD are sporadic but rare cases are familial, with earlier onset. The underlying mechanisms and causes of PD still remain unclear.